A tessera hospitalis from the oppidum of Monte Bernorio (Villarén de Valdivia, Palencia) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The oppidum of Monte Bernorio occupies a strategic location in the southern territory of the ancient Cantabri. Archaeological research has revealed it as one of the most important Iron Age fortified towns in the central Cantabrian region. Data have been collected for its defensive structures, urbanism and ways of life, spanning from the Late Bronze Age to the Late Iron Age. A recently appeared tessera hospitalis sheds new light on this kind of alliance in the Cantabrian region, as well as on the language spoken by these communities.
Keywords: Monte Bernorio; Late Iron Age; Tessera Hospitalis; Celtic language